(untitled) (Eurasian Scientific Herald, 2024)
This article provides information on the unique appeal of the Finnish education system, the teacher education curriculum that teachers in Finland currently follow, as well as its main principles, and how to study in Finland. the historical foundations of teacher education are explained. In the conclusion part, Finnish education and our country’s education system are compared.